Hot surface ignition and combustion characteristics of sprays in constant volumecombustion chamber using various sensors. Issue 1 (1st January 2018) - Rehman, Sanaur
Abstract: In present study, ignition and combustion characteristics of hollow conical diesel fuel sprays are studied experimentally in constant volumecombustion chamber using hot surface ignition technique at various operating conditions. Sensor based measurement techniques like needle lift sensor, photo (optical) sensor and piezoresistive pressure transmitter sensor are used to measure the ignition, combustion and injection characteristics. In this study, hot surface temperatures (HST) varied from 623 to 723 K, cylinder air pressures (CP) varied from 20 to 40 bar and fuel injection pressures varied from 100 to 400 bar. It is found that ignition and combustion characteristics are significantly affected by fuel injection characteristics. Luminous ignition delays (ID) of the diesel sprays significantly reduced with the increase in hot surface temperatures and cylinder air pressures and variation is non-linear. Effect on ID mitigates as hot surface temperature and cylinder air pressure rise to higher values. Rate of heat release (at maximum pressure) rises with increase in hot surface temperatures but decreases with rise in cylinder air pressures. Rate of heat release increment is minimized as hot surface temperature increases. Also, rate of heat release reduces with increase in cylinder air pressure. Duration of burn/combustion reduced with increase in cylinder air pressures and hot surface temperatures. At higher surface temperature, the effect of surface temperature on duration of burn mitigates. Peak pressure increases with rise in hot surface temperatures. Hence, hot surface ignition effect on ignition and combustion characteristics of sprays substantially mitigates at higher surface temperature, which are typical operating conditions of small size high-speed direct injection diesel engines.